Analysis Of Financed Customers Investment For Millennial Entrepreneurs In The Field Of MSMES - Arisah, Nur; Andi Izatul Fiddah; Riski Aprilianti Baharuddin; Rizka Rayhana Burhan; Dillah Faradilla Hasanah (International Journal of Education, Vocational and Social Science, 2023)
The formulation of the problem from this study, how is the interest/interest of University of Patompo students in investing in investor customers in the Indonesian capital market? Therefore, this study will find out the investment of investor customers in millennial entrepreneurs in the MSME sector, especially University of Patompo students who are studying in the fields of economics. This study is a type of descriptive research. The data collection technique in this study uses an open interview technique. Before and after asking the respondents, the researcher had obtained the respondent's consent regarding the confidentiality of the answers given. The results of this study indicate that University of Patompo students are still lacking in investing.